Restorative Justice Treatment for Domestic Violence Crimes: A Qualitative Study - Barocas, Briana (Criminal justice and behavior, 2023)
Domestic Violence Intervention Programs have become a key component in addressing domestic violence (DV) crimes. Recent research suggests that combining standard intervention programs with other approaches can improve overall effectiveness. The aim of this study was to examine the experiences of individuals court-mandated to treatment who completed either a standard intervention program or a restorative justice (RJ)-based hybrid intervention program combining a standard treatment program with RJ elements and Circles of Peace. Multiple interviews were conducted with participants (N = 14) who completed one of the two programs. Qualitative data analysis was performed. Four major themes emerged: Communication and understanding, Changes in the nature of the violence, Changes in self-perception, and Program content and atmosphere experiences. The findings suggest that the hybrid intervention program may have a positive influence on the way participants perceive treatment effectiveness. Participants’ experiences may serve as a framework for improving approaches to DV treatment.